Pengaruh Penggunaan Leaflet sebagai Media Edukasi terhadap Peningkatan Pengetahuan dan Perilaku Ibu Hamil tentang Hepatitis B di Wilayah Kerja Puskesmas Melintang Tahun 2025 - Cindi Aulia (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Hepatitis is an inflammation of the liver cells that can be caused by various factors, such as alcohol consumption, autoimmune disorders, drugs, or toxins. Viral infections, such as hepatitis A virus (HAV), hepatitis B virus (HBV), hepatitis C virus (HCV), hepatitis D virus (HDV), and hepatitis E virus (HEV). WHO estimates that by 2022, about 254 million people worldwide will be chronically infected with hepatitis B, with 1.2 million new infections occurring each year. In the same year, hepatitis B caused the deaths of about 1.1 million people, mostly due to cirrhosis and liver cancer. Hepatitis is very dangerous, therefore pregnant women really need to know about Hepatitis B disease and have positive behavior about Hepatitis B so that they can take precautions to prevent transmission to both the mother and the fetus. The purpose of this study was to determine the effect of using leaflets as educational media on increasing the knowledge and behavior of pregnant women about Hepatitis B in the Melintang Health Center Working Area. This type of research uses the Quasy Experimental Design method with pre-test and post test groups where observations are made twice, namely experiment and after experiment. Observations made before the experiment, namely observation 1 (O1) called the pre-test and after the experiment, namely observation 2 (O2) called the post test. Based on the results of the study, it was found that there was an effect of using leaflets as educational media on increasing knowledge (P = 0.000) and behavior (p = 0.000) of pregnant women about Hepatitis B in the Melintang Health Center Working Area in 2025. So it can be concluded that there is an effect of using leaflets as educational media on increasing the knowledge and behavior of pregnant women about Hepatitis B in the Melintang Health Center Working Area in 2025.